Longitudinal evaluation of criteria for subjective cognitive decline and preclinical Alzheimer's disease in a memory clinic sample. Issue 1 (16th May 2017) - Eckerström, Marie; Göthlin, Mattias; Rolstad, Sindre; Hessen, Erik; Eckerström, Carl; Nordlund, Arto; Johansson, Boo; Svensson, Johan; Jonsson, Michael; Sacuiu, Simona; Wallin, Anders
Abstract: Introduction: Subjective cognitive decline (SCD) and biomarker‐based "at‐risk" concepts such as "preclinical" Alzheimer's disease (AD) have been developed to predict AD dementia before objective cognitive impairment is detectable. We longitudinally evaluated cognitive outcome when using these classifications. Methods: Memory clinic patients ( n  = 235) were classified as SCD ( n  = 122): subtle cognitive decline ( n  = 36) and mild cognitive impairment ( n  = 77) and subsequently subclassified into SCDplus and National Institute on Aging–Alzheimer's Association (NIA‐AA) stages 0 to 3. Mean (standard deviation) follow‐up time was 48 (35) months. Proportion declining cognitively and prognostic accuracy for cognitive decline was calculated for all classifications. Results: Among SCDplus patients, 43% to 48% declined cognitively. Among NIA‐AA stage 1 to 3 patients, 50% to 100% declined cognitively. The highest positive likelihood ratios (+LRs) for subsequent cognitive decline (+LR 6.3), dementia (+LR 3.4), and AD dementia (+LR 6.5) were found for NIA‐AA stage 2. Discussion: In a memory clinic setting, NIA‐AA stage 2 seems to be the most successful classification in predicting objective cognitive decline, dementia, and AD dementia.